Sustainability in the Prato Textile District: Vanguard and Tradition - Margherita Tufarelli; Renato Stasi; Debora Giorgi; Maria Claudia Coppola (Pad, 2022)
The contribution takes part in the vast panorama of research and initiatives to investigate the way for a more sustainable, ethical, and democratic fashion system. The Prato District is acknowledged as “the textile district par excellence” (Becattini, 2000) thanks to its profound link to environmental sustainability throughout its history. The district stands out since the Middle Ages for its ancient recycling techniques paired with its traditional figures, such as “cenciaioli”. Today the tradition has been reinterpreted in a modern key and strengthened by the birth of several new firms dedicated to the production or processing of recycled and regenerated fabrics. The growing awareness of consumers on ethical and environmental issues offers this survey the possibility to suggest a development path for the circular textile industry to face the transition into the New Normal.